The Surprising Complexity of Virus-Host Cell Interaction Revealed by the Powerful Systems Biology Approaches of Genomics and Proteomics - Rustanti, Lina (Central Basic Biomedical and Health Technology, 2013)
Understanding interaction between viruses and host cells during infection process is the first step in discovering appropriate drugs and vaccines against viral diseases. Advance technologies based on genomics and proteomics approaches provide great tools to disclose the complexity of virus-host interaction. In this essay, the application of RNAi screens method and proteomics-based approaches on influenza virus will be elucidated as an example. Using those methods, the primary factors controlling viral replication pathway were discovered. These findings are useful for the development of potential strategies to overcome viral diseases.Keywords : virus, host, pathogen, interaction, genomic, proteomic.Â AbstrakMemahami interaksi antara virus dan pejamu dalam proses infeksi merupakan langkah awal dalam upaya penemuan obat dan vaksin yang tepat untuk melawan penyakit yang disebabkan oleh virus. Pendekatan teknologi berbasis genomik dan proteomik merupakan terobosan yang dapat menjawab kompleksitas interaksi virus-pejamu. Dalam kajian ini, akan dibahas penerapan teknologi screening RNAi dan teknologi berbasis proteomik pada virus influenza. Dengan menggunakan metode ini, faktor-faktor utama yang mengontrol tahap replikasi virus akan dapat ditemukan. Penemuan ini sangat bermanfaat dalam pengembangan strategi pengobatan yang potensial untuk mengatasi penyakit bersumber virus.Kata kunci: virus, pejamu, patogen, interaksi, genomik, proteomik.